Influence of tin addition by redox reaction in different media on the catalytic properties of Pt-Re/Al2O3 naphtha reforming catalysts - D'ippolito, Silvana Andrea (2009)
The influence of Sn addition by catalytic reduction method on the Pt-Re/Al2O3 properties for the n-C7 reforming reaction was studied. The Sn addition was performed in different media (HCl and H2O). It was found that trimetallic Pt-Re-Sn/Al2O3-Cl catalysts prepared in H2O or HCl medium present a good interaction between Sn and the catalytically active species (Pt-Re). This strong interaction of Sn with the active phase correlates with the lower hydrogenolytic and dehydrogenating activity of the trimetallic catalysts. Total acidity and Brønsted acidity decrease with the addition of Sn. The catalysts prepared in HCl have both higher Brønsted and total acidity in comparison to those prepared in H2O. In the case of catalysts prepared in HCl medium, the production of C2-C4 gases in the n-C7 reforming reaction also decreases upon Sn addition confirming that the cracking activity decreases when the acidity is decreased. In both trimetallic catalysts series a decrease in the toluene yield can be seen at high Sn contents. The production of toluene depends on the activity in dehydrocyclization reaction. Dehydrocyclization requires sites of lower acid strength than those needed for cracking. The addition of small amounts of Sn (≤0.2 wt%) would enable the step of sulfidation of Pt-Re/Al2O3 catalysts to be spared.